Cardiovascular mortality in bipolar disorder: a population-based cohort study in Sweden. Issue 4 (18th April 2013) - Westman, Jeanette; Hällgren, Jonas; Wahlbeck, Kristian; Erlinge, David; Alfredsson, Lars; Ösby, Urban
Abstract : Objective: To estimate the cardiovascular mortality among persons with bipolar disorder in Sweden compared to the general population. Design: Population register-based cohort study with a 20-year follow-up. Setting: Sweden. Participants: The entire population of Sweden (n=10.6 million) of whom 17 101 persons were diagnosed with bipolar disorder between 1987 and 2006. Main outcome measures: Mortality rate ratios (MRR), excess mortality (excess deaths), cardiovascular disorder (CVD) and specifically cerebrovascular disease, coronary heart disease, acute myocardial infarction, sudden cardiac deaths and hospital admission rate ratio (ARR). Results: Persons with bipolar disorder died of CVD approximately 10 years earlier than the general population. One third (38%) of all deaths in persons with bipolar disorder were caused by CVD and almost half (44%) by other somatic diseases, whereas suicide and other external causes accounted for less than a fifth of all deaths (18%). Excess mortality of both CVD (n=824) and other somatic diseases (n=988) was higher than that of suicide and other external causes (n=675 deaths). MRRs for cerebrovascular disease, coronary heart disease and acute myocardial infarction were twice as high in persons with bipolar disorder compared to the general population. Despite the increased mortality of CVD, hospital admissions (ARR) for CVD treatment were only slightly increased in persons with bipolar disorder when compared to the general population. Conclusions: The increased cardiovascular mortality in persons with bipolar disorder calls for renewed efforts to prevent and treat somatic diseases in this group. Specifically, our findings further imply that it would be critical to ensure that persons with bipolar disorder receive the same quality care for CVD as persons without bipolar disorder.